Evidence Supporting the Existence of a Distinct Obese Phenotype of Heart Failure With Preserved Ejection Fraction. Issue 1 (4th July 2017) - Obokata, Masaru; Reddy, Yogesh N.V.; Pislaru, Sorin V.; Melenovsky, Vojtech; Borlaug, Barry A.
Abstract : Background: Heart failure (HF) with preserved ejection fraction (HFpEF) is a heterogeneous syndrome. Phenotyping patients into pathophysiologically homogeneous groups may enable better targeting of treatment. Obesity is common in HFpEF and has many cardiovascular effects, suggesting that it may be a viable candidate for phenotyping. We compared cardiovascular structure, function, and reserve capacity in subjects with obese HFpEF, those with nonobese HFpEF, and control subjects. Methods: Subjects with obese HFpEF (body mass index ≥35 kg/m 2 ; n=99), nonobese HFpEF (body mass index <30 kg/m 2 ; n=96), and nonobese control subjects free of HF (n=71) underwent detailed clinical assessment, echocardiography, and invasive hemodynamic exercise testing. Results: Compared with both subjects with nonobese HFpEF and control subjects, subjects with obese HFpEF displayed increased plasma volume (3907 mL [3563–4333 mL] versus 2772 mL [2555–3133 mL], and 2680 mL [2380–3006 mL]; P <0.0001), more concentric left ventricular remodeling, greater right ventricular dilatation (base, 34±7 versus 31±6 and 30±6 mm, P =0.0005; length, 66±7 versus 61±7 and 61±7 mm, P <0.0001), more right ventricular dysfunction, increased epicardial fat thickness (10±2 versus 7±2 and 6±2 mm; P <0.0001), and greater total epicardial heart volume (945 mL [831–1105 mL] versus 797 mL [643–979 mL] and 632 mL [517–768 mL]; P <0.0001), despite lower N-terminal pro-B-type natriuretic peptide levels. Pulmonary capillary wedge pressure was correlated with body mass and plasma volume in obese HFpEF ( r =0.22 and 0.27, both P <0.05) but not in nonobese HFpEF ( P ≥0.3). The increase in heart volumes in obese HFpEF was associated with greater pericardial restraint and heightened ventricular interdependence, reflected by increased ratio of right- to left-sided heart filling pressures (0.64±0.17 versus 0.56±0.19 and 0.53±0.20; P =0.0004), higher pulmonary venous pressure relative to left ventricular transmural pressure, and greater left ventricular eccentricity index (1.10±0.19 versus 0.99±0.06 and 0.97±0.12; P <0.0001). Interdependence was enhanced as pulmonary artery pressure load increased ( P for interaction <0.05). Compared with those with nonobese HFpEF and control subjects, obese patients with HFpEF displayed worse exercise capacity (peak oxygen consumption, 7.7±2.3 versus 10.0±3.4 and12.9±4.0 mL/min·kg; P <0.0001), higher biventricular filling pressures with exercise, and depressed pulmonary artery vasodilator reserve. Conclusions: Obesity-related HFpEF is a genuine form of cardiac failure and a clinically relevant phenotype that may require specific treatments. Abstract : Supplemental Digital Content is available in the text.